2000
DOI: 10.1021/ja001915g
|View full text |Cite
|
Sign up to set email alerts
|

Aqua, Alcohol, and Acetonitrile Adducts of Tris(perfluorophenyl)borane:  Evaluation of Brønsted Acidity and Ligand Lability with Experimental and Computational Methods

Abstract: Equilibrium studies have been performed to determine the Brønsted acidity of [(C 6 F 5 ) 3 B(OH 2 )]‚ H 2 O, the aqua species that exists in acetonitrile solutions of B(C 6 F 5 ) 3 in the presence of water. NMR spectroscopic analysis of the deprotonation of [(C 6 F 5 ) 3 B(OH 2 )]‚H 2 O with 2,6-Bu t 2 C 5 H 3 N in acetonitrile allows a pK value of 8.6 to be determined for the equilibrium [(C 6 F 5 ) 3 B(OH 2 )]‚H 2 O a [(C 6 F 5 ) 3 B(OH)] -+ [H 3 O] + . On the basis of a calculated value for the hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
230
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(244 citation statements)
references
References 32 publications
11
230
0
3
Order By: Relevance
“…8,28 This cumulative body of evidence has resulted in a high degree of acceptance for this mechanism in the literature, but the specific nature of the adducts I, or encounter complexes of type II, remain experimentally opaque. 22 29 Si NMR spectroscopy at 233 K. Noting, however, that their procedures did not appear to involve careful drying of the borane before use, it seemed likely that the peak assigned to this adduct is due in fact to Et3SiOSiEt3, formed rapidly when wet borane 35,36 is treated with silane via rapid dehydrogenative silation of water. 37,38 We confirmed this postulate by recording the 29 Si NMR spectrum of an authentic sample of Et3SiOSiEt3.…”
mentioning
confidence: 99%
“…8,28 This cumulative body of evidence has resulted in a high degree of acceptance for this mechanism in the literature, but the specific nature of the adducts I, or encounter complexes of type II, remain experimentally opaque. 22 29 Si NMR spectroscopy at 233 K. Noting, however, that their procedures did not appear to involve careful drying of the borane before use, it seemed likely that the peak assigned to this adduct is due in fact to Et3SiOSiEt3, formed rapidly when wet borane 35,36 is treated with silane via rapid dehydrogenative silation of water. 37,38 We confirmed this postulate by recording the 29 Si NMR spectrum of an authentic sample of Et3SiOSiEt3.…”
mentioning
confidence: 99%
“…of C 6 F 5 H and CH 3 OB(C 6 F 5 ) 2 , whilst that of the former was slower, proceeding to the boroxin [OB(C 6 F 5 )] 3 [18] (presumably via HOB(C 6 F 5 ) 2 ); all of these are identified as products in the completed reaction using 1 H, 19 Since the only labile source of protons in the decomposition reactions of 3 and 4 is the TMPH cation, this suggests that recombination of the ion pairs to form TMP and ROH·B(C 6 F 5 ) 3 (R = CH 3 , H) must occur (Scheme 4); corroborating this hypothesis is the detection of H 2 O·B(C 6 F 5 ) 3 H-bonded with various anions in the MS(ES). [19] Whilst studies have shown that such adducts can dissociate to give ROH and free B(C 6 F 5 ) 3 , [20] at these temperatures protonation of the ipso-C on the C 6 F 5 rings appears to be faster (yielding ROB(C 6 F 5 ) 2 and C 6 F 5 H), which preclude any catalytic turnover. Finally, addition of one equivalent of CO 2 to a 1:1 mixture of TMP/B(C 6 F 5 ) 3 (4 eq., excess, under H 2 atmosphere) in C 7 D 8 demonstrated quantitative conversion to CH 3 OB(C 6 F 5 ) 2 via 2, after 6 days at 160°C.…”
mentioning
confidence: 99%
“…[26][27][28] Light-induced catalysis is of particular importance in the area of photolithography, where photoacid generators (PAGs) eject protons upon irradiation, 29,30 which mediate the deprotection of photoresist polymers and allow for patterning to sub-20 nm resolution. Given the importance of B(C 6 F 5 ) 3 and other perfluoroaryl boranes as Lewis acid catalysts for siloxane synthesis and modification, we became interested in devising molecules that, when irradiated, would liberate this borane. In other words, we sought photo Lewis acid generators, or "PhLAGs".…”
Section: ð1þmentioning
confidence: 99%
“…33 Therefore, PhLAG molecules that are thermally robust and produce a well-defined Lewis acid efficiently are of potential value in materials synthesis. In a preliminary communication, 34 we reported preparation of the first PhLAG molecule capable of the photorelease of B(C 6 F 5 ) 3 and applications of this design to photoinduced hydrosilylation and Piers-Rubinsztajn catalysis. The compound was a triphenylsulfonium-carbamatoborate ion pair, 1-Ph 3 S (Chart 1), which decomposes under irradiation with 254 nm light to release one equivalent of B(C 6 F 5 ) 3 , along with other products that were innocuous in terms of desired hydrosilation catalysis.…”
Section: ð1þmentioning
confidence: 99%
See 1 more Smart Citation